Transforming the Education Workforce: Learning teams for a learning generation - Education Commission (Education Commission, 2019)
The Education Commission's vision to strengthen, diversify, and transform the education workforce to deliver inclusive, quality education for all.
KerkoCite.ItemAlsoKnownAs: 2339240:HFEU63QF 2339240:KAFI2DU8 2339240:Y46JESVZ 2405685:7JBG673D 2405685:AG66GV8B 2405685:J99WFZ9L 2405685:MF5UMTVS 2405685:PBVSSI2T 2405685:RZINF2DS 2534378:UMCUKS9F
Keywords: C: International; ___working_potential_duplicate

Universal Basic Education 2018 Indicator Profile for Basic Education Institutions in Nigeria: Public Schools Commission - Universal Basic Education Commission (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:V8XHE9D4 2405685:DE29EEVB